(untitled) (African Journal of Biomedical Research, 2023)
Facet tropism is the difference in orientations between the right and left facet joints and has been argued to play a causative role in disc herniation. This study aimed to determine the association between facet tropism and lumbar disc herniation among black Africans. This was a comparative study of 136 patients with low back pain, comprising 91 cases with disc herniation and 45 controls showing normal discs. Axial and sagittal T2-weighted images obtained from a 0.36-Tesla MRI scanner were used for evaluation. Facet angles were measured using the method described by Noren et al and a substantial facet tropism was defined as a difference of mean + 1SD (Standard Deviation) between the bilateral facet joint angles obtained in the controls. A disc herniation was defined as a focal prolapse of disc material beyond the posterior vertebral margin within 90 degrees of disc circumference. Of the 91 images evaluated, herniated disc was noted at the L1/L2 level in 8 cases; L2/L3 in 31; L3/L4 in 62; L4/L5 in 88, and at L5/S1 in 58, with many cases showing multilevel disc prolapse. Adjusting for the effects of age and gender, multiple logistic regression was performed to determine the difference in mean facet tropism between the cases and the controls. Greater degree of facet tropism was noted among the cases compared to controls at all lumbar motion segments (p<0.05). Facet tropism among black Africans is associated with lumbar disc herniation at all the lumbosacral motion segments.